2005
DOI: 10.1111/j.1365-2702.2005.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse consultants: their characteristics and achievements

Abstract: The findings show that holders of such posts need to have appropriate previous knowledge, skills and personal characteristics, as these seem to influence their ability to integrate the four domains of the role and thus achieve the requirements of the post.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 10 publications
6
103
0
Order By: Relevance
“…Table 2 demonstrates some qualities that were surprising, in that they did not show up more strongly (though it is acknowledged that wording may be used differently between participants). Problem solver, can think on their feet (15) Desire for continuous improvement (14) Good communicator (13) Resilient / persistent (12) Thick skinned (11) Think before acting (11) Strong belief / vision (11) Clinical expert with experience (10)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 demonstrates some qualities that were surprising, in that they did not show up more strongly (though it is acknowledged that wording may be used differently between participants). Problem solver, can think on their feet (15) Desire for continuous improvement (14) Good communicator (13) Resilient / persistent (12) Thick skinned (11) Think before acting (11) Strong belief / vision (11) Clinical expert with experience (10)…”
Section: Resultsmentioning
confidence: 99%
“…Ford (10) reported these characteristics to be determination, perseverance, motivation, strength of character and emotional intelligence. Similarly in nursing, Woodward, Webb and Prowse (15) included:…”
Section: Introductionmentioning
confidence: 99%
“…These posts will vary slightly across the UK, but all should have at least 50% clinical commitment. Previous work has identified that undertaking research, interpreting research and translating findings into clinical practice still remained a challenge (Charters et al, 2005;Woodward et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This notion of autonomy was analysed by Braddock and Sawyer (1985) and Crowley (1989), who suggest that external/independent consultants may discover that rather than gaining autonomy, they face a greater number of constraining forces in the external environment that will impose control over their work and thus stifle their autonomy. Today, the notion of autonomy in consultancy is underpinned by the nurses' preparation and education before taking on the role (Woodward et al, 2005;2006), effective interpersonal skills (Abbott 2007;McSherry et al, 2007) and a transformational leadership approach (McIntosh and Tolson, 2009;Young et al, 2010).…”
Section: Gallessich's Model Of Consultancymentioning
confidence: 99%